Compósitos de grafite a base poliuretana modificados com SBA-15 na determinação dos antioxidantes BHA e TBHQ em biodiesel - OLIVEIRA, Danielle Cristina Vasconcelos de (2017)
Due to the importance of the antioxidants to guarantee the quality of the biodiesel, by the parameters of its oxidative stability, analytical methodologies have been developed to quantitatively evaluate the antioxidants present in the biodiesel matrices. In this work SBA-15 and Ni- SBA-15 (nickel incorporated in the SBA-15) were synthesized by the hydrothermal method and characterized, being used as modifier (2.5%) in polyurethane graphite based electrochemical sensors to compare their Performance in determining the antioxidants BHA (3-tert-butyl-4-hydroxyanisole) and TBHQ (tert-butylhydroquinone). Among the sensors used, the GPU electrode modified with SBA-15 was the one that presented the best response in the determination of the antioxidants in the preliminary tests, being then applied in the determination of the antioxidants in the biodiesel sample, using the technique of Differential Pulse Voltammetry (DPV ), Using BR as buffer pH = 2 as the electrolyte. The proposed method presented a linear response in the antioxidant determinations (0.993, for TBHQ determinations and 0.977 for BHA determinations), good results for the limit of detection (LOD BHA = 1, (2.03 for determinations of TBHQ and 2.13 for determinations of BHA) and accuracy (102.5% for determinations of TBHQ and 98, 97% for BHA determinations).